Pengaruh Gaya Kepemimpinan, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV Bali Coral Di Banyuwangi - Nur Hasanah; Hary Sulaksono; Hayatul Masfufah (JMBI : Jurnal Manajemen Bisnis dan Informatika, 2022)
This study aims to determine the effect of Leadership Style, Motivation, and Work Environment on Employee Performance at CV Bali Coral in Banyuwangi. The population in this study are all employees at CV Bali Coral in Banyuwangi. The sample used is 64 employees or respondents who are employees at CV. Bali Coral in Banyuwangi. Technique the sampling used is Non Probability Sampling With the sample method census (saturated). The test used is the data instrument test (validity test and test). reliability), classical assumption test (normality test, multicollinearity test, and test heteroscedasticity), Coefficient of Determination (R2), and t test, the analytical technique that used is Multiple Linear Regression analysis. Data analysis method using the help of SPSS 20. The results showed that the f . test results statistically it can be proven that the independent variable Style Leadership, Motivation and Work Environment simultaneously affect significant impact on employee performance at CV Bali Coral in Banyuwangi. Results T-Test Leadership Style and Motivation and Work Environment Influence partially on Employee Performance at CV Bali Coral.